THE EFFECT OF ANCHORING BIAS AND HERDING BEHAVIOR ON STOCK INVESTMENT DECISIONS AMONG GENERATION Z IN INDONESIA: THE MEDIATING ROLE OF RISK PERCEPTION - Khalif Mahaztra; Dewi Rahmayanti (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study investigates the effects of anchoring bias and herding behavior on stock investment decisions among Generation Z investors in Indonesia, with risk perception as a mediating varable. Research Methodology: A quantitative approach was employed using primary data collected via online questionnaires distributed to 200 active Generation Z stock investors across Indonesia, selected through purposive sampling. Data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. Results: Anchoring bias exerted the strongest overall influence on both risk perception and investment decisions, followed by herding behavior and respectively). Risk perception significantly and positively mediated both relationships and also exerted a direct positive effect on investment decisions, confirming its dual role as both a psychological mediator and an independent predictor of decision quality. Conclusions: Cognitive (anchoring) and social (herding) biases jointly shape Generation Z stock investment decisions in Indonesia, both directly and through the calibrating mechanism of risk perception, extending prospect theory by showing that elevated risk awareness sharpens rather than suppresses decision quality among digital native investors. Limitations: This study is limited to active Generation Z stock investors. The model explains 35.9% of the variance in risk perception, indicating that additional determinants remain unexplored. Moreover, the cross-sectional design and reliance on self-reported data limit causal inference and may introduce common method bias. Contributions: This study advances behavioral finance by confirming risk perception as a dual mediator between anchoring bias, herding behavior, and investment decisions among Generation Z investors in Indonesia